115 Persistence of Infarct Zone Oedema at 6 Months after Acute ST-elevation Myocardial Infarction: Incidence, Pathophysiology and Association with Left Ventricular Remodelling. (3rd June 2016) - Carberry, Jaclyn; Carrick, David; Haig, Caroline; Rauhalammi, Sam; Ahmed, Nadeem; Mordi, Ify; McEntegart, Margaret B; Petrie, Mark; Eteiba, Hany; Hood, Stuart; Watkins, Stuart; Lindsay, Mitchell; et al.
Abstract : Background: The natural history of persistent myocardial oedema after ST-elevation myocardial infarction (STEMI) is uncertain. Methods: and ResultsPatients who sustained an acute STEMI were enrolled in a cohort study (BHF MR-MI; ClinicalTrials.gov: NCT02072850 ). Cardiac magnetic resonance (CMR) imaging with T2-mapping of myocardial oedema was performed at 1.5 Tesla 2 days and 6 months post-MI. Myocardial oedema was defined as infarct signal intensity (S. I.) >2 standard deviations from the mean S. I. within a remote reference region. 283 STEMI patients (mean (SD) age 59 (12) years, 75% male) were enrolled. Infarct size was 18 (13)% of left ventricular (LV) mass. At 2 days, infarct zone T2 (ms) was higher than remote zone T2 (62.9 (5.2) vs. 49.7 (2.1); p < 0.001), and this relationship persisted at 6 months (56.2 (4.1) vs. 49.7 (2.3); p < 0.001). Mean remote zone T2 did not change over time (p = 0.840) whereas infarct zone T2 decreased (p < 0.001). At 6 months, infarct zone oedema persisted in 177 (63%) patients who were more likely to have a history of hypertension (regression coefficient (95% confidence interval) 1.77 (0.99, 3.13); 0.053) and a larger initial size of infarction (1.02 (1.00, 1.05); p = 0.020) but less likely to have a history of previous PCI (0.28 (0.08, 0.99); p = 0.049), compared to patients without persistent oedema. In a multivariate analysis, infarct zone oedema at 6 months was associated with an increase in LV end-diastolic volume (9.68 (3.76, 15.61); p = 0.001). Conclusion: Persistence of oedema within the infarct zone affected the majority of patients at 6 months post-STEMI, and was associated with the initial severity of STEMI and adverse LV remodelling.